Impaired cognitive control over emotional material in euthymic bipolar disorder - Wolkenstein, Larissa; Kanske, Philipp; Bailer, Josef (Journal of affective disorders, 2017)
Background: Previous research suggests that bipolar disorder (BD) is characterized by deficits in cognitive control (CC). Impaired CC has been found in high-risk samples and is associated with the maintenance of BD symptoms. It remains unclear, however, whether BD is characterized by a general deficit in CC or by a deficit that is specifically related to the processing of emotional material. Methods: The sample consisted of 42 remitted bipolar patients and 39 healthy controls (HC). We examined whether BD individuals display impaired CC when confronted with negative as well as positive material using an arithmetic inhibition task that required inhibition of pictorial stimulus material. Results: Whereas both groups showed difficulties in exerting CC over negative material, only BD individuals exhibited deficient CC over positive material. Limitations: Even though we intended the negative and positive pictures in the arithmetic inhibition task to be similarly arousing, participants in the current study rated the negative compared to the positive pictures as more arousing. Conclusions: BD is associated with impaired CC when processing emotional - especially positive - stimuli even when patients are in remission. Possible implications of this deficit especially for emotion regulation are discussed.
Gesehen am 30.04.2018